The territorial dimension of environmental sustainability in Italy along the urban–rural continuum. Issue 8 (3rd July 2018) - Coderoni, Silvia; Pagliacci, Francesco
Abstract : Single territories contribute in different ways to the transition towards a more environmentally sustainable development (SD), according to their structural features. This study returns a multi-dimensional picture of the territorial divides of environmental sustainability across Italy, analysing how it correlates with rurality, with a focus on the urban–rural continuum. Italy represents an interesting case study because of its peculiar territorial urban–rural structure. We first assess the environmental sustainability targets across Italian NUTS 3 regions and their capital cities using two composite sustainability indexes, by referring to both standard values (i.e. conforming to legislation) and optimum values (i.e. desired values). Then, we investigate the relationship between environmental sustainability and rurality. Results suggest that a positive link between the two exists, being stronger at city level. Among major policy implications, the environmental dimensions of territorial cohesion should be integrated more strongly in key European policies to reach a more balanced SD.